2015
DOI: 10.1515/cclm-2014-0944
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of EDTA carryover during blood collection

Abstract: An EDTA carryover during blood collection using a closed vacuum system is highly unlikely. Even if carryover of EDTA whole blood occurs, an absolute volume larger than 10 μL would be necessary to alter test results. However, contamination of samples with preloaded pure K3EDTA solution by severe neglect of current recommendations in blood collection may significantly alter testing results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 11 publications
1
17
0
1
Order By: Relevance
“…EDTA is used at approximately 1.5 mg/mL or 5 mM 34 and thus will undoubtedly confound assay results with Cu 2 L. EDTA is not known to readily extract copper(II) ions from other polydentate ligands, but as a hexadentate ligand itself, it is not surprising that it can displace eosin Y. 35 Regardless, this finding underscores the risk of exaggerating the selectivity of a chemosensor.…”
Section: Resultsmentioning
confidence: 99%
“…EDTA is used at approximately 1.5 mg/mL or 5 mM 34 and thus will undoubtedly confound assay results with Cu 2 L. EDTA is not known to readily extract copper(II) ions from other polydentate ligands, but as a hexadentate ligand itself, it is not surprising that it can displace eosin Y. 35 Regardless, this finding underscores the risk of exaggerating the selectivity of a chemosensor.…”
Section: Resultsmentioning
confidence: 99%
“…Underfilling of the tubes (tubes filled with less than 90% of draw volume) is strongly discouraged and should be avoided. Although some would argue that incorrect order of draw when using closed blood collection systems is not the source of contamination [77,78], there is firm evidence showing that contamination still occurs more commonly than might be expected and can be difficult to identify [79][80][81][82]. This is probably because venepuncture is not always performed under ideal conditions.…”
Section: Samplingmentioning
confidence: 99%
“…Cadamuro et al . found that a simulated carryover of 1 µL of K 3 EDTA blood reduced calcium by 13% ( 21 ). According to Cadamuro et al , EDTA whole blood carryover is highly unlikely, and, even if it occurs, it would be needed a larger volume than 10 µL to alter test results.…”
Section: Discussionmentioning
confidence: 99%